Pelos caminhos de Oblivion: representação e resistência da cultura caipira e o ensino de História - Paiva, Rafaela Molina De [UNIFESP] (2019)
The present work is a study of local history as a methodological approach in the teaching of history. Starting from the pedagogical necessity lived in the middle school of the interior of the State of São Paulo, specifically, of the municipality of Areias, Serra da Bocaina region, in the Paraíba Valley of São Paulo. The theme chosen to be analyzed and developed in the classroom was the country culture. According to the theoretical-methodological conception adopted here, it is important to work with local history projects in the teaching of history as an alternative strategy to the prescribed curriculum of the State of São Paulo. Caipira culture was chosen as a theme, since it is a subject present in the imaginary and daily representations of the Paraíba Valley, especially those living in the rural region called the Historical Valley. Region where the country's culture is preserved and resists, in contrast to the advance of industrial production, capital and globalization. Let us realize with this work that the various local and cultural temporalities overlap, and preserve cultural and local identities. Studying the ancient literary city of Monteiro Lobato, Oblivion (Areias), the city of Jéca Tatú, made me a teacher-researcher, after all, I proposed to work with the local caipira culture with my high school students, but, given the lack of research and information on the subject, I had to look at local history and introduce my students to these investigations. This pedagogical practice has transformed history teaching into something more exciting, enjoyable, alive and close to the regional and cultural reality of the students. Approached the skills and content prescribed by the curricula to the reality lived by the student.